2004
DOI: 10.1128/aem.70.3.1555-1562.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Tetracycline Resistance in Enterococcus Isolates from Food

Abstract: In the present study, a collection of 187 Enterococcus food isolates mainly originating from European cheeses were studied for the phenotypic and genotypic assessment of tetracycline (TC) resistance. A total of 45 isolates (24%) encompassing the species Enterococcus faecalis (n ‫؍‬ 33), E. durans (n ‫؍‬ 7), E. faecium (n ‫؍‬ 3), E. casseliflavus (n ‫؍‬ 1), and E. gallinarum (n ‫؍‬ 1) displayed phenotypic resistance to TC with MIC ranges of 16 to 256 g/ml. Eight of these strains exhibited multiresistance to TC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
118
1
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(146 citation statements)
references
References 51 publications
20
118
1
7
Order By: Relevance
“…have demonstrated inducible resistance to antimicrobials such as chloramphenicol, enrofloxacin, erythromycin, and tetracycline (Huys et al, 2004;Leener et al, 2005). Many of these resistance genes are located on transferable sections of DNA (plasmids), which can be exchanged between different Enterococcus isolates (Huys et al, 2004). Although determining specific resistance genes for antimicrobial agents was outside the scope of this study, the phenotypic resistance characteristics seen in this study closely parallel previously reported genetic characteristics of Enterococcus.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…have demonstrated inducible resistance to antimicrobials such as chloramphenicol, enrofloxacin, erythromycin, and tetracycline (Huys et al, 2004;Leener et al, 2005). Many of these resistance genes are located on transferable sections of DNA (plasmids), which can be exchanged between different Enterococcus isolates (Huys et al, 2004). Although determining specific resistance genes for antimicrobial agents was outside the scope of this study, the phenotypic resistance characteristics seen in this study closely parallel previously reported genetic characteristics of Enterococcus.…”
Section: Discussionsupporting
confidence: 74%
“…In addition to innate resistance, Enterococcus spp. have demonstrated inducible resistance to antimicrobials such as chloramphenicol, enrofloxacin, erythromycin, and tetracycline (Huys et al, 2004;Leener et al, 2005). Many of these resistance genes are located on transferable sections of DNA (plasmids), which can be exchanged between different Enterococcus isolates (Huys et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Purified tet(M) amplimers were sequenced directly with the DI, DII and TetM-R primers (Gevers et al, 2003;Huys et al, 2004) in order to obtain a 1420 bp partial sequence (74 % of the 1920 bp open reading frame) of the tet(M) gene. Sequencing was performed with a BigDye Terminator version 2 Ready Reaction cycle sequencing kit (Applied Biosystems) on an ABI Prism 310 Genetic Analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, it has been shown that the tet(M) gene can display several mosaic structures, leading to the recognition of at least five different sequence homology groups (SHGs I-V) (Gevers et al, 2003;Huys et al, 2004). In order to investigate whether any of these SHGs are also represented in the four tet(M)-containing Listeria strains of this current study, the open reading frame of this gene was partially sequenced and aligned with a selection of tet(M) reference sequences (Fig.…”
Section: Genetic Diversity Of Tet(m) Genes In Listeriamentioning
confidence: 99%
“…Hence, the investigation of LAB antibiotic resistance patterns may represent an effi cient tool in predicting the antibiotic resistance among clinical pathogens. Extensive literature data pointed out that genes conferring resistance to several antimicrobials (i.e., chloramphenicol, erythromycin, streptomycin, tetracycline, and vancomycin), hosted on mobile genetic elements, have been characterized in lactococci [44], lactobacilli [45,46] and enterococci [47,48] from food.…”
Section: Discussionmentioning
confidence: 99%